PENGGUNAAN METODE LATIHAN UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPA SISWA KELAS VI SD NEGERI 001 UKUI SATU KECAMATAN UKUI - Suyatin ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This background is the low class VI student learning outcomes SD Negeri 001 Ukui Satu Kecamatan Ukui. This research is a class action, the study was conducted in two cycles. This study aims to improve science learning outcomes through the implementation of training methods. The data used in this research is data teacher and student activities and student learning outcomes IPA. Based on the results of the study, data showed that the activities of teachers and students and learning outcomes IPA increased in each cycle. This is evidenced by: (a) the activities of teachers in each cycle increases, in the first cycle obtained a score of 19 (63%) with a category (simply perfect) and in cycle II increased with a score of 22 (73%) with katedori (perfect), Besides the student activity also increased, in the first cycle obtained a score of 47 (60%) with a category (high) and the second cycle obtain a score of 52 (67%) with a category (high); and (b) Results to learn science is also increased, as evidenced by the increase in the number of students learning completeness, in the first cycle the number of students who reached the KKM is 10 students (77%) and the second cycle a total of 11 students (85%).